Sosiologi Ruang Konseling Religius di SMP Islam: Studi Kolaborasi Guru BK, Guru PAI, dan Orang Tua dalam Pendampingan Remaja MTS NU 1 Purwokerto - Muh. Hanif; Ghinaa Syifaa Ariibah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the role of religious counseling spaces in Islamic junior high schools as collaborative arenas involving counseling teachers, Islamic education teachers, and parents in assisting adolescents. The research problem arises from the reality that some students experience low self-confidence, learning difficulties, social problems, and emotional challenges that cannot always be resolved solely through psychological approaches. This study aims to explain the empirical practices of religious counseling, the social relationships involved within it, and its implications for religious education in schools. The research employed a collaborative case study with a qualitative approach. Data were collected through observations, interviews with Islamic education teachers, counseling teachers, students, and parents, as well as documentation in the form of counseling records and student development programs. The findings reveal that student cases are addressed through a combination of psychological approaches and religious guidance, while parents are actively involved to strengthen behavioral changes at home. Counseling records and development programs also indicate an integration between personal guidance and religious education. Therefore, religious counseling spaces function not only as places for solving students’ problems, but also as spaces for meaning-making, social control, and strengthening adolescents’ religious character. These findings are consistent with recent studies emphasizing the importance of school-family collaboration, a sense of safety in counseling, and the integration of religious values into guidance and counseling services.